M2 Currents And Residual Flow In The Gulf Of California - Quirós, Guillermo (1992)
The full nonlinear, vertically-averaged equations of motion are time integrated through a finite difference scheme on a regular grid that reproduces the topography of the Gulf of Califor nia with a mesh size of 14 km. The model is forced through a remote, open-ocean boundary to the south by a linear superposition of the incoming and outgoing Kelvin waves of the M2 tide. Fric tion, parameterized by a quadratic depth dependent law, and a viscosity close to 103.m2.s -I, suffice to stabilize the model. The resulting maps of tidal elevations and phase agree adequately with those drawn by other authors from coastal observations. The computed tidal flows are dominated by the effects of the large bathymetric gradients; the currents acceler ate markedly in the narrows and straits around the Gulf's large islands, and effects of resonance and bottom friction are evident in the shallow north ern Gulf. An average of the computed flow over an integral number of tidal cycles yields a residual circulation with typical values two orders of mag nitude smaller than those of the instantaneous flow, organized in basin-wide closed cells with ad jacent gyres rotating in opposite senses. The lar gest cell is a counterclockwise gyre found in the northern Gulf, which is probably driven by a trans fer of tidal vorticity to the mean field through a bottom frictional torque. Residual flows are also important in the region of the large islands where the rectification is induced by the large topo graphic gradients in the channels and sills. The M2 residual circulation should remove a passive tracer from the upper Gulf in several months, or close to one year. No appreciable residual effects of the M2 tide are observed in the southern part of the Gulf.